2015
DOI: 10.1038/srep11521
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chiral polymorph A-enriched zeolite Beta with an extremely concentrated fluoride route

Abstract: Chiral zeolitic materials with intrinsically chiral frameworks are highly desired because they can combine both shape selectivity and enantioselectivity. In the field of zeolite, the synthesis of chiral polymorph A of zeolite Beta or chiral polymorph A-enriched zeolite Beta is one of the biggest challenges. We demonstrate here a generalized extremely concentrated fluoride route for the synthesis of chiral polymorph A-enriched zeolite Beta in the presence of five achiral organic structure-directing agents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 33 publications
(45 reference statements)
2
44
0
Order By: Relevance
“…The first signal at −37.7 ppm is due to the fluoride ion occluded in the D4R cage, whereas the latter two signals are attributed to the fluoride ions occluded in the [4 3 5 4 ] cage of S-Beta zeolite sample. Due to be short of D4R cage in S-Beta zeolite sample, the detected D4R in the sample is most likely associated with the existence of the two adjacent layers at least stacked with the manner in polymorph C, which is in good agreement with the literature [15]. 29 Si and (c) 19 F MAS NMR spectra of as-synthesized S-Beta sample after water treatment.…”
Section: Synthesis Of S-beta Zeolitesupporting
confidence: 77%
See 1 more Smart Citation
“…The first signal at −37.7 ppm is due to the fluoride ion occluded in the D4R cage, whereas the latter two signals are attributed to the fluoride ions occluded in the [4 3 5 4 ] cage of S-Beta zeolite sample. Due to be short of D4R cage in S-Beta zeolite sample, the detected D4R in the sample is most likely associated with the existence of the two adjacent layers at least stacked with the manner in polymorph C, which is in good agreement with the literature [15]. 29 Si and (c) 19 F MAS NMR spectra of as-synthesized S-Beta sample after water treatment.…”
Section: Synthesis Of S-beta Zeolitesupporting
confidence: 77%
“…Up to now, all silica Beta zeolite is still hydrothermally synthesized in the presence of water solvent and costly organic templates [14][15][16]. For example, Wang et al reported an all silica Beta zeolite synthesis in the presence of a large number of water as solvent and costly TEAOH (aqueous solution) as organic templates in hydrothermal condition [16].…”
Section: Introductionmentioning
confidence: 99%
“…SEM and high-resolution TEM (HRTEM) have proven to be highly advantageous methods for analyzing crystallite morphologies. HRTEM has been used previously to analyze the polymorph domains in *BEA (16,20). However, specific chiral space groups (i.e., structural enantiomers) within the detected polymorph A domains were not able to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports involving the enrichment of polymorph A in *BEA (which does not guarantee enantioenrichment), characterization of any true structural enrichment of polymorph A has been limited to transmission electron microscopy (TEM) analysis (PXRD analyses are fraught with problems) of the polymorph domains and demonstration of enantioenrichment by measuring some function (e.g., catalysis or adsorption) (15,16). A distinct issue with this methodology, however, is that the synthesis of these materials lacks proper controls with regard to the enantiomorphs obtained in the product materials, and therefore it is not possible to perform appropriate analytical and experimental controls to confirm chirality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation